Icelandic Constitutional Reform 2010–2020 - Wszołek, Anna (Studia Scandinavica, 2021)
The Icelandic constitution was passed on June 17, 1944. Amendments were passed in 1959, 1984, 1991, 1995, and, 1999. None of them introduced any significant changes to the original document. The financial crisis of 2008 caused a decline in public trust of politicians and the existing political system in Icelandic society. Icelanders began to demand a review of the constitution. Constitutional reform began in 2010 and continues to this day. The Icelandic constitution was passed on June 17, 1944. Amendments were passed in 1959, 1984, 1991, 1995, and, 1999. None of them introduced any significant changes to the original document. The financial crisis of 2008 caused a decline in public trust of politicians and the existing political system in Icelandic society. Icelanders began to demand a review of the constitution. Constitutional reform began in 2010 and continues to this day.